2007
DOI: 10.1194/jlr.m500481-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Electronegative LDLs from familial hypercholesterolemic patients are physicochemically heterogeneous but uniformly proapoptotic

Abstract: A highly electronegative fraction of human plasma LDLs, designated L5, has distinctive biological activity that includes induction of apoptosis in bovine aortic endothelial cells (BAECs). This study was performed to identify a relationship between LDL density, electronegativity, and biological activity, namely, the induction of apoptosis in BAECs. Plasma LDLs from normolipidemic subjects and homozygotic familial hypercholesterolemia subjects were separated into five subfractions, with increasing electronegativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 39 publications
4
24
0
1
Order By: Relevance
“…Another possible mechanism responsible for the partial loss of LDLr affi nity is the chemical modifi cation of Lys in apoB-100 of LDL(-). There is some controversy regarding the presence of mild oxidative modifi cation in LDL(-) ( 5 ); however, the degree of oxidation reported by most authors is lower (23)(24)(25) than that necessary for extensive modifi cation of Lys by MDA ( 17,19 ). In agreement with these observations, current data of MDA-Lys reactivity showed that Lys in LDL(-) were not differentially modifi ed by oxidation-related mechanisms compared with LDL(+).…”
Section: Discussionsupporting
confidence: 80%
“…Another possible mechanism responsible for the partial loss of LDLr affi nity is the chemical modifi cation of Lys in apoB-100 of LDL(-). There is some controversy regarding the presence of mild oxidative modifi cation in LDL(-) ( 5 ); however, the degree of oxidation reported by most authors is lower (23)(24)(25) than that necessary for extensive modifi cation of Lys by MDA ( 17,19 ). In agreement with these observations, current data of MDA-Lys reactivity showed that Lys in LDL(-) were not differentially modifi ed by oxidation-related mechanisms compared with LDL(+).…”
Section: Discussionsupporting
confidence: 80%
“…The most electronegative subfraction of LDL can be obtained using fast‐protein liquid chromatography with anion‐exchange columns to fractionate human LDL into five subfractions with increasing electronegativity, called L1 to L5 (Chen et al., 2003; Ke et al., 2011). The most electronegative subfraction, L5, is the only LDL subfraction that can induce endothelial dysfunction and atherogenic responses in cultivated arteries and cultured vascular cells or impair normal differentiation of endothelial progenitor cells (Chen et al., 2007; Chu et al., 2013; Lu et al., 2008; Stancel et al., 2016). These biochemical properties of L5 have been attributed to its lipid and protein composition, enzymatic activities, and structural features (Ke, Stancel, Bair, & Chen, 2014; Ke et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…20,[28][29][30] LDL(-) (a lipid peroxidation marker) induces atherogenesis by a variety of biological activities including cytotoxicity and leukocyte recruitment that actively contribute to the alteration of the vascular endothelium, increasing CV risk. [8][9][10] Many reports have described the increased LDL(-) levels in patients with CV disease risk, including CKD.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 LDL(-) is a plasma-circulating LDL subfraction, minimally modified, that can be an initiating factor of atherosclerosis by actively contributing to alteration of the vas-cular endothelium and induce the cell death, thus increasing CV risk. [8][9][10] Many reports have described the relationship between an increase in LDL(-) levels and increased CV disease risk in patients with hypercholesterolemia and diabetes mellitus. [10][11][12] Our group also found high-LDL(-) levels in patients undergoing hemodialysis (HD), 13 suggesting that this increased levels of LDL(-) could be involved in the progress of the atherogenic process in CKD patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation